PARTISIPASI MASYARAKAT DALAM PERENCANAAN RUANG TERBUKA HIJAU DI KELURAHAN BUKIT TUNGGAL KOTA PALANGKA RAYA - Noor Hamidah; Waluyo Nuswantoro; Mahdi Santoso; Tatau Wijaya Garib (Universitas Jenderal Soedirman, 2020)
Green Open Space and parks are a balance system between nature and humans in the built area. The concept of green space and parks is a balancing of decreasing open space, and increasing the area built. To improve the balance of the environment and built area, green space in the built area, especially settlements, needs to be restored in order for the two systems to play an optimal role. Parks and green space is a response to the needs of the landscape in a residential area and urban areas. The need for green space and parks is ideally an integrated ecological, social, and economic aspects of the urban area. Community participation proposal aims to show the role of community participation in the utilization of the needs of parks and green space in a residential area for ecological, economic and social sustainability in the future. The proposed community service involves community participation in the management of green space and parks as open space in a residential area in Bukit Tunggal Village, Jekan Raya District, Palangka Raya City. The method is a qualitative focus on observing community participation from the preparation, implementation and post-implementation stages of the implementation of the concept of green space and tree planting and garden arrangement in housing of the Bukit Tunggal village in an integrated manner according to the needs of open space for community activities and environmental preservation.